The Injury-Related Activation of Hedgehog Signaling Pathway Modulates the Repair-Associated Inflammation in Liver Fibrosis - Shen, Xin; Peng, Yu; Li, Hanmin (Frontiers in Immunology, 2017)
Liver fibrosis is a wound-healing response driven primarily by inflammation in response to various iterative parenchymal injuries caused by diverse etiologies. Immune cells have been identified as key players in the fibrotic cascade, with the capacity to exert either injury-inducing or repair-promoting effects. A characteristic feature of the fibrotic microenvironment associated with chronic liver injury is aberrant activation of Hedgehog signaling pathway. Growing evidence from a number of different studies in vivo and in vitro has indicated that immune-mediated events involved in liver fibrogenesis are regulated by Hedgehog signaling pathway. In this review, we emphasize the impacts of injury-activated Hedgehog signaling on liver fibrogenesis through modulating repair-related inflammation, and focus on the regulatory action of aberrant Hedgehog signaling on repair-related inflammatory responses mediated by hepatic classical and non-classical immune cell populations in the progression of liver fibrosis. Moreover, we also assess the potentiality of Hedgehog pathway inhibitors as good candidates for anti-fibrotic therapeutic agents because of their immune-regulation actions for liver fibrogenic repair. The identification of immune regulatory mechanisms of Hedgehog signaling pathway underlying the fibrotic process of chronic liver diseases might provide a basis for Hedgehog-centered therapeutic strategies for liver fibrosis.